No differences in cycling efficiency detween world-class and recreational cyclists - Moseley, L.; Achten, J.; Martin, J. C.; Jeukendrup, A. E. (International Journal of Sports Medicine, 2004)
The aim of this experiment was to compare the efficiency of elite cyclists with that of trained and recreational cyclists. Male subjects (N = 69) performed an incremental exercise test to exhaustion on an electrically braked cycle ergometer. Cadence was maintained between 80 - 90 rpm. Energy expenditure was estimated from measures of oxygen uptake (VO2) and carbon dioxide production (VCO2) using stoichiometric equations. Subjects (age 26 ± 7 yr, body mass 74.0 ± 6.3 kg, Wpeak 359 ± 40 W and VO2peak 62.3 ± 7.0 mL/kg/min) were divided into 3 groups on the basis of their VO2peak (< 60.0 (Low, N = 26), 60 - 70 (Med, N = 27) and > 70 (High, N = 16) mL/kg/min). All data are mean ± SE. Despite the wide range in aerobic capacities gross efficiency (GE) at 165 W (GE165), GE at the same relative intensity (GEfinal), delta efficiency (DE) and economy (EC) were similar between all groups. Mean GE165 was 18.6 ± 0.3 %, 18.8 ± 0.4 % and 17.9 ± 0.3 % while mean DE was 22.4 ± 0.4 %, 21.6 ± 0.4 % and 21.2 ± 0.5 % (for Low, Medium and High, respectively). There was no correlation between GE165, GEfinal, DE or EC and VO2peak. Based on these data, we conclude that there are no differences in efficiency and economy between elite cyclists and recreational level cyclists.